Simulasi Perancangan Antena UWB (Ultra Wide Band) Untuk Mendeteksi Tumor Payudara - Eko Prasetio; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In recent years, the development of ultra-wideband (UWB) technology for biomedical and diagnostics at microwave frequencies has become an interesting issue. Ultra-wideband (UWB) is a communication that has a low transmit power, avoiding danger to human health. In this paper, an ultra-wideband microstrip (UWB) antenna is designed to detect breast tumors, which operates at a frequency of 5.8 Ghz with a frequency range of 5 to 6 Ghz. The substrate used is FR-4. From the simulation results, the frequency obtained is 5.61 with a return loss of -33.47 dB. Moreover, the bandwidth and gain obtained are 3.46 GHz and 2.96 dB, respectively.Keyword: ultra-wideband, Microstrip antenna, UWB antenna, Breast tumor.